ثر تزاحم حقوق الامتياز في تحديد مراتبها في القانون المدني الجزائري. - مريم, تومي (جامعة الوادي.University eloued, 2021)
كد المشرع المدني الجزائري في المادة 982 منه بأن الامتياز أولوية يقررها القانون، فيمنح صاحبه حق التقدم والتتبع في أي يد يكون باعتباره حق عيني تبعي، وقد جاءت حقوق الامتياز مصنفة ومرتبة وفق سلم، ترتيبا تنازليا، من أعلى السلم إلى أسفله مراعيا دواعي منح هذا الحق امتيازا على غيره، وهي حقوق امتياز عامة وحقوق امتياز خاصة واقعة على المنقول في المواد 990 إلى 998 مدني جزائري وحقوق امتياز خاصة واقعة على العقار في المواد 999 إلى 1001 منه، لذلك جاءت وفق سبع مراتب إضافة إلى مرتبة حقوق الامتياز العقارية الخاضعة للقيد، ولتحديد مراتب حقوق الامتياز أثر بالغ وحل ناجع لحالات تزاحم هذه الحقوق، أين يتعدد أصحاب الحقوق والديون الممتازة لاستيفاء حقوقهم من الذمة المالية للمدين، دون أن تتسع لوفائها كلها، لذلك أكدنا بوضوح على حالتي تزاحم الحقوق الممتازة فيما بينها أين يراعى الترتيب الوارد عند المشرع المدني وأحكام نصوصه، إذ عند تزاحم حقوق ممتازة فيما بينها ومن نفس المرتبة تعتمد قاعدة القسمة قسمة غرماء، أما حالة تزاحم الحقوق الممتازة مع الديون المضمونة برهن، فإنه لا يحتج بحق امتياز على حائز المنقول حسن النية، بينما تتقدم الامتيازات العامة المعفاة من الشهر على كل الرهون، أما الخاضعة للشهر فتكون الأولوية بالأسبق في تاريخ القيد. The Algerian civil legislator affirmed in Article 982 of it that the concession is a priority determined by the law, so it grants its owner the right to advance and follow in any hand as it is a right in kind. Privileges over others, which are general privileges and special privileges on the movable in Articles 990 to 998 Algerian civilians and special privileges on the property in Articles 999 to 1001 thereof, so they came according to seven ranks in addition to the rank of real estate privileges subject to restriction, and to determine the ranks of Franchise rights have a significant impact and an effective solution to cases of competing rights, Where are the holders of privileged rights and debts numerous in order to fulfill their rights from the debtor’s financial liability, without extending to all of them, so we have clearly emphasized the two cases of competing rights among them, where the arrangement mentioned in the civil legislator and the provisions of its texts are taken into account, because when competing rights between them and of the same rank depend The rule of division is dividing by debtors. As for the case of competition of privileged rights with debts secured by a mortgage, it does not invoke a privileged right on the bona fide movable holder, while the general privileges exempted from the month take precedence over all mortgages. The Algerian civil legislator affirmed in Article 982 of it that the concession is a priority determined by the law, so it grants its owner the right to advance and follow in any hand as it is a right in kind. Privileges over others, which are general privileges and special privileges on the movable in Articles 990 to 998 Algerian civilians and special privileges on the property in Articles 999 to 1001 thereof, so they came according to seven ranks in addition to the rank of real estate privileges subject to restriction, and to determine the ranks of Franchise rights have a significant impact and an effective solution to cases of competing rights, Where are the holders of privileged rights and debts numerous in order to fulfill their rights from the debtor’s financial liability, without extending to all of them, so we have clearly emphasized the two cases of competing rights among them, where the arrangement mentioned in the civil legislator and the provisions of its texts are taken into account, because when competing rights between them and of the same rank depend The rule of division is dividing by debtors. As for the case of competition of privileged rights with debts secured by a mortgage, it does not invoke a privileged right on the bona fide movable holder, while the general privileges exempted from the month take precedence over all mortgage
مجلد 12 العدد 02
Keywords: حق الامتياز، التزاحم، المرتبة، القيد، الدائن الممتاز; Franchise, rivalry, rank, constraint, preferred creditor.